How to find HIV AIDS information for adolescent - Herlin Fitriana Kurniawati; Herlin Fitriani Kurniawati; Fayakun Nur Rohmah; Nuli Nuryanti Zulala (International Journal of Health Science and Technology, 2019)
HIV and AIDS case have increased while the knowledge of adolescents still low, this is a problem in handling cases of HIV and AIDS. The purpose of this research is to find out an overview of internet usage to search an information about HIV and AIDS. The research method uses a qualitative approach, a type of descriptive analytic research, a cross sectional approach. The subjects of this research were adolescents who accessed information about HIV and AIDS using the internet for at least the last 6 months and were willing to become respondents. Sampling techniques using purposive sampling. The results show that knowledge about HIV and AIDS is still lacking, especially in the signs and symptoms and transmission of HIV and AIDS, there is still a stigma against people with HIV and AIDS. All informants said that using the internet on their own initiative, most of the informants said that using the internet was approximately 2-5 hours a day, on average using the internet more than 2 years ago. Most respondents said that they had sought information about HIV and AIDS even if they were not intense only if they needed it. Suggestions for health cadres are expected to be able to propose the formation of Adolescent Family Development (BKR) or the Adolescent Reproductive Health Counseling Center (PIK-KRR) in collaboration with the District and BKKN District.